PENGARUH PEMBERIAN NECK CALLIET EXERCISE TERHADAP PENURUNAN NYERI LEHER PADA PEGAWAI ADMINISTRASI DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS HILIDUHO TAHUN 2020 - Isidorus Jehaman; Martha Putri Mendrofa; Sabirin Berampu; Siti Sarah Bintang (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Neck pain is a collection of symptoms related to degenerative processes as well as those that are not related to degenerative processes such as poor positioning in job activity, direct trauma or repetitive micro-trauma. In helping to reduce neck pain in patients, the treatment given is neck cailliet exercise. To find out the influence of neck cailliet exercise to decrease neck pain in administration. This research is a quantitative study, a pseudo-experimental quasi by using the one group pre-Test post-Test design, having a sample of 18 respondents with a total sampling technique. Data analysis obtained using T-Test paired sample test which obtained the mean result prior to the administration neck Cailliet exercise is 5.50 with a standard deviation of 0.985 and the mean after giving neck cailliet exercise is 3.44 with a standard deviation 0.856, which means there is a decrease in neck pain after given the neck cailliet exercise with P value = 0.000 (P < 0.05). Result showed that the giving of neck cailliet exercise was influential for the reduction of neck pain in administration. Conclusion: giving neck cailliet exercise is very effective against reduction of neck pain in administration. Suggestion: The patient must re-apply the instruction given by the physiotherapy at home